2020
DOI: 10.2147/idr.s263082
|View full text |Cite
|
Sign up to set email alerts
|

<p>Genotypic Distribution and a Potential Diagnostic Assay of Multidrug-Resistant Tuberculosis in Northern Thailand</p>

Abstract: Introduction: Knowledge of the prevalence and distribution of multidrug-resistant tuberculosis (MDR-TB) genotypes in northern Thailand is still limited. An accurate, rapid, and cost-effective diagnostic of MDR-TB is crucial to improve treatment and control of increased MDR-TB. Materials and Methods: The molecular diagnostic assays named "RIF-RD" and "INH-RD" were designed to detect rifampicin (RIF) and isoniazid (INH) resistance based on real-time PCR and high-resolution melting curve analysis. Applying the ∆T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 22 publications
6
16
1
Order By: Relevance
“…In comparison, our study in Can Tho found no substitution in this codon. However, our study detected a substitution mutation at codon 532 that causes rifampicin resistance, while prior studies had not found it [22][23][24][25]27,[29][30][31][32][33][34][35] . Fitzgibbon, Margaret M., et al 2021 revealed mutations in Condon 532 26 ; however, the study's conclusion was due to the detection error of Xpert ® MTB/RIF Ultra.…”
Section: Country or Regioncontrasting
confidence: 58%
See 2 more Smart Citations
“…In comparison, our study in Can Tho found no substitution in this codon. However, our study detected a substitution mutation at codon 532 that causes rifampicin resistance, while prior studies had not found it [22][23][24][25]27,[29][30][31][32][33][34][35] . Fitzgibbon, Margaret M., et al 2021 revealed mutations in Condon 532 26 ; however, the study's conclusion was due to the detection error of Xpert ® MTB/RIF Ultra.…”
Section: Country or Regioncontrasting
confidence: 58%
“…Table 8 compares the difference in mutant genotypes of rifampicin-resistant TB bacteria in our study to studies from other geographical regions. Codon 526 is one of the most prevalent mutations in the RRDR of the rpoB gene [25][26][27][28] . Mutations at codon 526 had been found in previous studies 23,25,27,[29][30] .…”
Section: Country or Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the WHO-endorsed GeneXpert was widely used in this region, allowing for the rapid diagnosis of MDR-/RR-TB cases compared with the speed of conventional phenotypic methods. 30 Second, all identified MDR-TB patients were hospitalized until bacterial conversion was verified by smear microscopy. Significant reductions in the bacterial load of sputum samples can reduce the transmission of MDR-TB in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Globally in 2019, an estimated 465,000 incident cases were reported as MDR and rifampicin resistant (RR) TB, while 3.3% and 13% of new cases and 18% and 17.4% of previously treated cases were diagnosed with MDR/RR TB and isoniazid (INH) resistant TB, respectively (World Health Organization 2020). Thailand is one of the top 14 countries with high TB, TB/HIV and MDR-TB and had 150 TB cases per 100,000 population in 2019 (World Health Organization 2020) (Anukool et al 2020).…”
Section: Introductionmentioning
confidence: 99%